Interactions and stabilisation of acetone, sulfur dioxide and water with 1-octyl-3-methylimidazolium tetrafluoroborate [OMIM][BF4] at low temperatures - Buckley, Matthew; Syres, Karen Louise; Jones, Robert G. (Royal Society of Chemistry, 2017)
The interactions between three small molecules, water (H2O), sulfur dioxide (SO2) and acetone ( (CH3)2CO ) with the ionic liquid (IL) 1-octyl-3-methylimidazolium tetrafluoroborate, [OMIM][BF4], have been determined using line of sight temperature programmed desorption (LOSTPD) from a gold surface. Multilayers of the IL were deposited by physical vapour deposition with multilayers of the small molecular species (adsorbed from the gas phase) at 90 K. LOSTPD was then carried out with the small molecular species desorbing first from the mixed multilayer, followed at higher temperatures by desorption of the IL from the gold surface. The IL had a high activation energy for desorption of 126(6) kJ mol-1 . Pure acetone showed a desorption activation energy of 38(2) kJ mol-1, which increased to 45 - 61 kJ mol-1 when it was pre-adsorbed below an overlying porous layer of the ionic liquid at 90 K. The stabilised acetone is thought to be associated with pores containing ionic moieties. Destabilised acetone was also observed and thought to originate from pores containing octyl chains. The quantity of stabilised acetone scaled with the amount of IL, being ≈ 1.1 molecules per IL ion pair. SO2 and H2O were co-adsorbed with the IL at 90 K leading to an intimate mixture of the two. For pure SO2 the desorption energy was 32(2) kJ mol-1, which increased to 40 - 50 kJ mol-1 for relative concentrations up to 6 SO2 molecules per IL ion pair. For pure water the activation energies were 49(5) kJ mol-1 and 43(1) kJ mol-1 for amorphous and crystalline ice respectively. When co-adsorbed with the IL the stabilisation energies were 42 - 49 kJ mol-1, but up to 505 water molecules per IL ion pair could be stabilised to some degree. The desorption mechanisms and the reasons for these interactions are discussed.